Multi-band magnitude complementary crossover network by using Q-Bernstein filter - Dolchai Sookcharoenphol; K. Janchitrapongvej (My University, 2024)
This paper presents a multi-band Magnitude Complementary (MC) crossover network by using Q-Bernstein filter (QBF). The prototype low-pass filter is used the Q-Bernstein Polynomial (QBP) to approximate a desired function. The QBF gives parameters which can be changing stop-band attenuation of the filter. The magnitude responses show that the filter gives high attenuation values in the stop-band of degree two. The two-band MC crossover network can be realized by cascading an all-pass filter and a constant voltage of degree one, which sums up to the All-Pass Filter (APF) of degree two. The multiple-bands crossover network can be realized by cascading two identical all-pass filter stages of degree two. The simulation results show that the proposed crossover network has a constant summed magnitude response and also an in-phase response over an audio band.
Keywords: Advanced Fiber Optic Sensors